PENERAPAN SENSOR ACCELEROMETER UNTUK MEMBANDINGKAN GEMPA DATA BMKG DAN GOOGLE EARTHQUAKE PADA PERANGKAT SMARTPHONE ANDROID - Putra, Anna Arthdi; Irawaty, Mardiana (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2014)
The earthquake that occurred around the world, generally always cause building damage and casualties. The number of fatalities occurred due to the lack of early notification and earthquakes happen very quickly. The software developed in this study can detect the strength of the earthquake. Magnitude detection software is designed to be equipped smartphone device accelerometer sensors and GPS. Smartphone users who apply this device will allow earthquake information (magnitude) faster than BMKG. The experimental results with comparison earthquakes that have occurred naturally suggest the software can be applied to well. Users of smartphones equipped with an accelerometer and GPS that applying this software can improve alertness when it will take place.